Iowa RBA, October 14-October 21, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA updates for October 14 and October 21, 1996. Highlights of the two updates include sightings of a female Surf Scoter, Western Grebes, White-winged Scoters, a Prairie Falcon, and a Red Phalarope. Also included are handwritten notes for the next two updates with sightings of a Sabine's Gull, Horned Grebes, American Avocets, and a Black-bellied Plover. Epson - sheet feed/flatbed